2010
DOI: 10.1111/j.1462-2920.2010.02273.x
|View full text |Cite
|
Sign up to set email alerts
|

The metavirome of a hypersaline environment

Abstract: Hypersaline environments harbour the highest number of virus-like particles reported for planktonic systems. However, very little is known about the genomic diversity of these virus assemblages since most of the knowledge on halophages is based on the analysis of a few isolates infecting strains of hyperhalophilic Archaea that may not be representatives of the natural microbiota. Here, we report the characterization, through a metagenomic approach, of the viral assemblage inhabiting a crystallizer pond (CR30) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
114
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(118 citation statements)
references
References 43 publications
4
114
0
Order By: Relevance
“…As in many previously studied hypersaline systems (12,34,39,57), our study site, Lake Tyrrell (LT), Victoria, Australia, is dominated by halophilic Archaea, including Haloquadratum walsbyi (40; S. Podell, J. A. Ugalde, P. Narasingarao, J. F. Banfield, K. B. Heidelberg, and E. E. Allen, unpublished).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As in many previously studied hypersaline systems (12,34,39,57), our study site, Lake Tyrrell (LT), Victoria, Australia, is dominated by halophilic Archaea, including Haloquadratum walsbyi (40; S. Podell, J. A. Ugalde, P. Narasingarao, J. F. Banfield, K. B. Heidelberg, and E. E. Allen, unpublished).…”
mentioning
confidence: 99%
“…Several haloviral morphologies have been observed through transmission electron microscopy (TEM) analysis, including spindle shaped (the most abundant form), spherical, icosahedral, filamentous, and headtail (41,61). Recently, metagenomic techniques have been applied to the study of viral communities (17,27), and in hypersaline systems, such studies have suggested that viral communities are relatively diverse (14,49,57,61) and show some global conservation (57,61). However, given the poor representation of viruses in public databases (52) and the lack of a universal marker gene for viruses, it is difficult to track viral populations across samples.…”
mentioning
confidence: 99%
“…The extension of analysis beyond viral metagenomic data sets alone to include other techniques to allow complete genome sequencing, virus isolation, and host identification directly from environmental samples greatly extends the utility of viral metagenomic data sets. Even though many of the tools and approaches described here have been used by others in isolation (21,28,41,71,72), no other studies to our knowledge have combined them to identify and initially characterize a new virus starting with only viral metagenomic data. To our knowledge, this is the first example of linking a virus genome to both particle morphology and a host with confirmation by culturing, effectively closing the viral metagenomic loop.…”
Section: Discussionmentioning
confidence: 99%
“…These findings demonstrate the value of viral metagenomics at the gene, community, and population levels to inform viral ecology. Viral metagenomic studies of acidic hot springs (17)(18)(19) and hypersaline environments (20,21) have led to the discovery of partial and full genomes of new archaeal viruses as well as viral groups formed by the clustering of related metagenomic contigs and estimates of total virus community diversity (18,22).…”
mentioning
confidence: 99%
“…A novel short rod-shaped virus, APBV1, was characterised from the thermoneutrophile Aeropyrum pernix which carries an exceptionally small genome of 5278 bp and has been classified into a new family the Clavaviridae [72]. Several seminal metagenomic studies have been performed examining the viral contents of extreme environments and attempting to link archaeal viral genome sequences to specific virion morphotypes both in terrestrial hotsprings [73,74] and in a hypersaline environments [75,76]. In the near future such studies, particularly when exploiting high throughput sequencing techniques, should provide many important breakthroughs.…”
Section: Afterwordmentioning
confidence: 99%